Tapered Cross‐Section Photoelectron Spectroscopy of State‐of‐the‐Art Mixed Ion Perovskite Solar Cells: Band Bending Profile in the Dark, Photopotential Profile Under Open Circuit Illumination, and Band Diagram. (18th May 2020) - Wussler, Michael; Mayer, Thomas; Das, Chittaranjan; Mankel, Eric; Hellmann, Tim; Prabowo, Chandra; Zimmermann, Iwan; Nazeeruddin, Mohammad Khaja; Jaegermann, Wolfram
Abstract: The purpose of this article is twofold. On the one hand the method of spacial resolved photoemission spectroscopy on small angle tapered cross‐sections (TCS) of complete devices is introduced to analyze simultaneously the chemical and electronic structure. On the other hand, a specific working principle of the analyzed cell type is revealed. Solar cells of 18% efficiency are prepared from a single precursor (FAPbI3 )0.85 (MAPbBr3 )0.15 with excess of 15% PbI2 . It is shown that TCS‐phototoelectron spectroscopy allows to determine the chemical composition as well as the potential distribution across the full device in the dark and in operation. The energy converting contact is the hole extraction back contact. Interestingly the photopotential in the analyzed cell type is predominantly created within the hole extraction layer and not in the n‐doped perovskite absorber. With the addition of measured core level to valence band maximum positions of the respective layers, TCS line scans lead to the band diagram for the full device. In addition, depth variations of the chemical composition are found: the bromide concentration increases while the iodide concentration is reduced near and within the mesoporous TiO2 layer. Abstract : Tapered cross‐section photoelectron spectroscopy is introduced as a new method to analyze complete electronic devices in thermodynamic equilibrium and in operation. The power of the method is demonstrated by analyzing a state‐of‐the‐art mixed ion perovskite solar cell in the dark and under illumination.